Money, Market and Systemic Causes of Poverty and Deprivation - Rab, Hifzur (University of Darussalam Gontor Press, 2025)
Real causes of growing poverty and deprivation are dominance of interest driven money depreciating capitalism and accounting in nominal terms. The system causes market failure in determination of just and efficient prices. These cause most of the surplus produced to be assigned to capital at the cost of share that goes to human capital especially the labour, while monetary depreciation (inflation) continues to eat away saving of the commoners. The system keeps prices of products and wages of the unorganised sector/developing and under developed countries relatively cheaper. Resultant concentration of wealth and power in hands of the rich/ developed countries allows them to ensure that favourable policies and programmes are adopted. These factors reinforce one other and even foreign trade lead to massive systemic transfer of wealth from poor and poor countries to the rich and developed countries. Massive transfer of wealth from poor to rich and from poor countries to rich countries keeps poverty and deprivation growing disregarding various poverty alleviation programmes worldwide. Dominance of this system together with failure of Islamic scholars to comprehend and address these problems especially monetary manipulation has compromised Islamic economic system that fails to manifest its truly just and efficient character